Petrology of the neoproterozoic, exo-granitic Kuiperskraal Sn-Zn-As deposit, Western Cape Province, South Africa - Bruwer, Louise (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1998.